2007
DOI: 10.1111/j.1748-1761.2007.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide, superoxide and renal blood flow autoregulation in SHR after perinatal L‐arginine and antioxidants

Abstract: Perinatal supplements shifted RBF autoregulation characteristics of SHR towards WKY, although capacity of the SHRsuppl kidney to modulate NO production to shear stress still seems impaired. The less strictly controlled RBF as observed in perinatally supplemented SHR could result in an improved long-term blood pressure control. This might partly underlie the beneficial effects of perinatal supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 28 publications
2
41
1
Order By: Relevance
“…Taken together, this is not a proof for but is compatible with increased afferent arteriolar resistance resulting in a partially suppressed FHH adult phenotype with respect to glomerular injury. This is quite the opposite of the response to arginine plus antioxidants that we observed in SHR where RVR was decreased by perinatal treatment (21). It remains unclear how in FHH limited exposure in early life to exogenous NO, a well-known vasodilator, can increase preglomerular resistance in adult life many months later.…”
Section: Discussioncontrasting
confidence: 56%
“…Taken together, this is not a proof for but is compatible with increased afferent arteriolar resistance resulting in a partially suppressed FHH adult phenotype with respect to glomerular injury. This is quite the opposite of the response to arginine plus antioxidants that we observed in SHR where RVR was decreased by perinatal treatment (21). It remains unclear how in FHH limited exposure in early life to exogenous NO, a well-known vasodilator, can increase preglomerular resistance in adult life many months later.…”
Section: Discussioncontrasting
confidence: 56%
“…11 Perinatal vitamin C and vitamin E alone had no persistent antihypertensive effects. 20 Our new data suggest that, because reduced expression of the renal cationic amino acid transporter could have limited the effect of L-arginine supplements in our previous study, antioxidative effects of taurine could have contributed substantially to the persistent effects. 11 Offspring of rat dams exposed to food restriction during pregnancy develop mild hypertension, and supplementation of L-arginine after weaning can reduce this blood pressure increase 21 and eventually even protect the kidneys.…”
Section: Discussionmentioning
confidence: 98%
“…Increased oxidative stress in hypertension promotes inflammation, vascular smooth muscle cell proliferation, and hypertrophy; impairs endothelium-dependent relaxation; and increases constrictive response to vasoactive agents [11,19,31]. Despite its genetic etiology, essential hypertension also results from adverse environmental factors, especially in the perinatal period [7,14,24,25,33]. The "programming hypothesis" proposes that adverse influences acting early in life, in particular in the intrauterine and postnatal period, leads to hypertension in adult life [1,10,17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of NO production are controversial, but it is generally accepted that NO bioavailability is decreased in SHR, possibly as a result of its inactivation by superoxide anions (O À 2 ) [12,13,27]. Despite the genetic predisposition, this imbalance during pregnancy and lactation also seems to play a role in the development of hypertension in SHR [14,24,25,33]. Racasan et al [24] have demonstrated that SHR offspring from L-arginine-and antioxidantssupplemented SHR dams had persistent lower blood pressure until 12 months of age.…”
Section: Introductionmentioning
confidence: 96%